Empowering Undergraduates through Technology: Designing and Implementing a Lecture Slides-Notes-Based Bucket List for Enhanced Productivity - Onwudebelu, Ugochukwu; Fasola, Olusanjo; Obinna-Isilebo, Chimnachi K (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
In today's academic landscape, students often rely on traditional methods of organization, such as notebooks and digital communication tools like WhatsApp, to manage their study materials. Moreover, undergraduates often face numerous challenges in managing their academic and personal responsibilities, leading to decreased productivity and increased stress. However, these methods can become cumbersome and inefficient, particularly as the volume of academic content increases. The challenges associated with organizing, accessing, and tracking progress on a diverse collection of materials can hinder student productivity and learning outcomes. To address this issue, we designed and implemented a slide and note based bucket list system (SANBLS) designed to enhance productivity among undergraduates utilizing Alex Ekwueme Federal University Ndufu Alike (AE FUNAI) as a case study. This tool aims to empower undergraduates by providing a structured framework for goal setting, organization, and time management. Furthermore, this paper seeks to create an intuitive application that offers enhanced features tailored to the needs of students. Key functionalities includes categorization of materials, allowing users to sort notes and slides into relevant topics or subjects, and a robust search capability that enables quick retrieval of specific content through keyword queries. The technical implementation of this project was grounded in object oriented analysis and design methodology (OOADM), which promotes modularity and ease of maintenance in code development. The application was built using the programming language Node.js for its server side capabilities, ensuring responsiveness and scalability. Firebase was employed for data storage, providing real time synchronization and efficient management of user data. Initial testing demonstrated that the program functions effectively when connected to the internet, receiving positive feedback from student users regarding its usability and functionality. However, to further enhance the application, future developments may include offline capabilities, allowing students to access their materials without relying on an internet connection. Ultimately, this research aims to revolutionize how students at AE FUNAI and potentially other institutions organize and engage with their academic materials. By streamlining access and tracking of notes and slides, the application aspires to significantly improve students' organizational skills, boost their productivity, and enhance their overall academic experience. Through continuous feedback and iterative development, this research seeks to adapt to the evolving needs of its users, ensuring that it remains a valuable resource throughout their academic journeys.